1985
DOI: 10.1002/actp.1985.010360302
|View full text |Cite
|
Sign up to set email alerts
|

Study of the structure of oriented blends of polypropylene and polyethylene obtained by the method of polymerization in situ combination

Abstract: The results of a study of oriented blends prepared by the method of successive synthesis of polypropylene and polyethylene with ZIEOLER-NATTA catalysts are presented. It is shown that the strong interaction of polypropylene and polyethylene allows to orient and maintain the oriented state of the polyethylene melt under static conditions for a long period of time. The partially oriented polyethylene melt is in liquid-crystalline state and crystallizes with extended chains. Die Struktur orientierter Mischungen v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Polyethylene, being an organic flexible-chain polymer, does not form a mesophase spontaneously when heated. To induce LC ordering, it is necessary to have a mechanical field retaining the chain in an unfold state above the melting point [19,20]. However, a thermodynamically stable existence of the mesomorphous state of the condis-crystalline (or condis-mesophase) type in the temperature range 303-600 K was found in polytetrafluoroethylenes which, as distinct from polyethylene, have carbon atoms framed with fluorine instead of hydrogen atoms [21].…”
Section: Thermodynamics and Structure Of Polyorganophosphazenesmentioning
confidence: 99%
“…Polyethylene, being an organic flexible-chain polymer, does not form a mesophase spontaneously when heated. To induce LC ordering, it is necessary to have a mechanical field retaining the chain in an unfold state above the melting point [19,20]. However, a thermodynamically stable existence of the mesomorphous state of the condis-crystalline (or condis-mesophase) type in the temperature range 303-600 K was found in polytetrafluoroethylenes which, as distinct from polyethylene, have carbon atoms framed with fluorine instead of hydrogen atoms [21].…”
Section: Thermodynamics and Structure Of Polyorganophosphazenesmentioning
confidence: 99%
“…or conformationally different from both the crystalline and the disordered amorphous phases, and its role in crystallization/melting and mechanical relaxation processes have been the subject of discussion for some decades already [2,3,5,7,[9][10][11][12][13][14]. Three (the high temperature α-relaxation and the low-temperature β-and γ-relaxation) relaxation processes lying below the melting temperature T m , and another thermal transition (termed λ) just above T m , i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This intermediate phase is also referred to as mesophase, interfacial or rigid amorphous phase [5]. A series of studies [13,14] showed that the melting/crystallization processes in flexible-chain polymers are actually more complicated than originally thought. X-ray diffraction measurements revealed that during heating, the crystalline phase of PE first transforms into a liquid crystal state and then into the true isotropic melt.…”
Section: Introductionmentioning
confidence: 99%